A year problem by Nihar

Algebra Level 3

( x ( x + 1 ) 2 ) 2 ( x ( x 1 ) 2 ) 2 = x 2 n \large \left(\dfrac{x(x+1)}{2}\right)^2 - \left(\dfrac{x(x-1)}{2}\right)^2=\dfrac{x^2}{n}

Let S n S_{n} be the sum of all values of x x that satisfy the above equation where n 0 n \ne 0 .

If S 2014 S_{2014} can be expressed as a b \dfrac{a}{b} where a , b a,b are coprime integers, then what is the value of a + b a+b ?

Bonus : generalize this for all n n .


The answer is 2015.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Nihar Mahajan
Apr 7, 2015

( x ( x + 1 ) 2 ) 2 ( x ( x 1 ) 2 ) 2 = x 2 2014 \left(\dfrac{x(x+1)}{2}\right)^2 - \left(\dfrac{x(x-1)}{2}\right)^2=\dfrac{x^2}{2014}

( x ( x + 1 ) 2 + x ( x 1 ) 2 ) ( x ( x + 1 ) 2 x ( x 1 ) 2 ) = x 2 2014 \Rightarrow \left(\dfrac{x(x+1)}{2} + \dfrac{x(x-1)}{2}\right)\left(\dfrac{x(x+1)}{2} - \dfrac{x(x-1)}{2}\right)=\dfrac{x^2}{2014}

( x 2 + x + x 2 x 2 ) ( x 2 + x x 2 + x 2 ) = x 2 2014 \Rightarrow \left(\dfrac{x^2+x+x^2-x}{2}\right)\left(\dfrac{x^2+x-x^2+x}{2}\right)=\dfrac{x^2}{2014}

( 2 x 2 2 ) ( 2 x 2 ) = x 2 2014 \Rightarrow \left(\dfrac{2x^2}{2}\right)\left(\dfrac{2x}{2}\right)=\dfrac{x^2}{2014}

x 3 x 2 2014 = 0 \Rightarrow x^3-\dfrac{x^2}{2014}=0

x 2 ( x 1 2014 ) = 0 \Rightarrow x^2\left(x-\dfrac{1}{2014}\right)=0

From this we get x = ( 0 , 1 2014 ) x=\left(0,\dfrac{1}{2014}\right) , hence

S 2014 = 1 2014 = a b S_{2014}=\dfrac{1}{2014}=\dfrac{a}{b}

a + b = 2015 \huge\Rightarrow \boxed{\color{#3D99F6}{a+b=2015}}

We also find that for this polynomial , S n = 1 n \huge S_n=\dfrac{1}{n}

Shouldn't Sn be 1/n instead of 1/(n+1) ?

Devin Ky - 6 years, 1 month ago

Log in to reply

Yeah... sorry for that!

Nihar Mahajan - 6 years, 1 month ago
Kyle Finch
Apr 7, 2015

Just for a change one can see this as sum of cubes of first x terms minus sum of cubes of first x-1 terms. This directly reduces the expression to x 3 = x 2 2014 x^3=\frac{x^2}{2014}

( x ( x + 1 ) 2 ) 2 ( x ( x 1 ) 2 ) 2 = x 2 2014 ( x 2 4 ) { ( x + 1 ) 2 ( x 1 ) 2 } = x 2 4 4 2014 2 x 2 = 4 2014 ( a 2 b 2 ) = ( a + b ) ( a b ) x = 1 2014 = a b . a + b = 2015 \large \left(\dfrac{x(x+1)}{2}\right)^2 - \left(\dfrac{x(x-1)}{2}\right)^2=\dfrac{x^2}{2014}\\\large \left(\dfrac{x^2}{4}\right)*\{(x+1)^2-(x-1)^2\}=\dfrac{x^2}{4}*\dfrac{4}{2014}\\\implies \large { {2x*2}=\dfrac{4}{2014} }~~~~~~\because (a^2-b^2)=(a+b)(a-b)\\x=\dfrac{1}{2014}=\dfrac{a}{b}.~~~~\therefore a+b= \large \color{#D61F06}{2015}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...